Edukasi Deteksi Dini Kanker Serviks melalui Pemeriksaan Inspeksi Visual dengan Asam Asetat pada Ibu Pemberdayaan dan Kesejahteraan Keluarga - Prayogo, Ahmad; Raudatul, Atun; Haniyah, Siti (Yayasan Inspirasi El Burhani, 2025)
Introduction: Cervical cancer is one of the leading causes of death among women, particularly in developing countries such as Indonesia. The lack of awareness regarding the importance of early detection is a key factor contributing to the high incidence of advanced-stage cervical cancer. Objective: The purpose of this service was to increase the knowledge and awareness of the PKK mothers in Sudimara Village regarding the importance of early detection of cervical cancer through IVA examination. Method: This public service was conducted by conducting a pre-survey, face-to-face counseling using animated video media, discussions, leaflet distribution, and knowledge evaluation through pre-test and post-test. The activity lasted for two days and involved 24 participants, aged 20–60 years. Result: There was a statistically significant increase in participants’ knowledge, with the average pre-test score of 60.42 rising to 79.17 on the post-test (mean difference 18.75; p < 0.05). The proportion of participants with high knowledge scores increased from 8.33% to 62.5% after the intervention. In addition, the number of participants who had undergone IVA examination increased from 20.8% to 37.5% after counseling. Conclusion: This result indicates that visual media-based education can improve understanding and encourage behavioral change related to early detection of cervical cancer. This activity is important to replicate and further develop to increase the coverage of IVA examination, as a preventive effort to reduce cervical cancer mortality rates at the community level.